Door seal particle made of vinyl polyolefin elastomer material, preparation method and door seal

By using vinyl polyolefin elastomer (EPOE), the problem of limited durability of existing TPE materials in low temperature environments is solved, the effect of maintaining good elasticity and physical strength in lower temperature environments is achieved, and the oil stain and water vapor barrier resistance is improved.

CN119735897AActive Publication Date: 2025-04-01合肥中科科乐新材料有限责任公司

Patent Information

Application Number
CN202510254376.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-01
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

The existing TPE materials have limited durability in low-temperature environments and are prone to swelling in oily substances, resulting in a decrease in elasticity and cannot meet the lower temperature application scenarios.

Method used

Door seal particles are prepared using vinyl polyolefin elastomer (EPOE) as raw material. EPOE has a lower glass transition temperature and higher branching degree to ensure good elasticity and physical strength under lower temperature environments.

Benefits of technology

EPOE door seal particles can still maintain good elasticity and physical strength under low temperature environments of -60℃, and have better oil stain resistance and water vapor barrier properties, extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention provides a door seal particle made of a vinyl polyolefin elastomer material, a preparation method of the door seal particle and a door seal, and belongs to the technical field of compositions of polyolefin and high-molecular compounds. The door seal particles made of the vinyl polyolefin elastomer material are prepared from the following components in parts by weight: 20 to 50 parts of white mineral oil, 10 to 48 parts of polypropylene, 10 to 50 parts of vinyl polyolefin elastomer, 5 to 25 parts of calcium carbonate, 0 to 0.1 part of antioxidant and 0 to 0.1 part of lubricant, wherein the branching degree of the vinyl polyolefin elastomer is 70-130 branched chains per 1000 carbons, the weight-average molecular weight is 77000-52.1 thousand, the molecular weight distribution index is 1.5-3.0, and the melt index is 1-10 g / 10 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of compositions of polyolefins and polymer compounds, and more specifically to the technical field of door seals for refrigerators and freezers, and in particular to door seal particles made of vinyl polyolefin elastomer, a preparation method, and a door seal. Background Art

[0002] Most of the door seals used in refrigerators and freezers on the market are made of soft polyvinyl chloride (PVC), and a small amount is made of thermoplastic elastomer (TPE). Compared with PVC, TPE material is more suitable for preparing refrigerator and freezer door seals. Specific reasons: First, TPE has excellent low temperature resistance (-24℃-4℃), and can still maintain good elasticity in low temperature environment; second, TPE has good anti-migration performance, and there will be no problem of plasticizer migration in PVC causing blister cracks or paint corrosion and adhesion; third, the molecular structure is stable, and the mechanical strength and elasticity are also better to reduce deformation and ensure the refrigeration effect; TPE has stronger anti-aging performance, and can still maintain good elasticity and appearance after long-term use, with a longer service life, and TPE is an environmentally friendly material.

[0003] The existing formula for preparing door seal particles using TPE materials contains styrene-ethylene / butylene-styrene block copolymer (SEBS), and the ethylene / butylene rubber segment (EB) in the middle of the molecular structure provides elasticity. In a low temperature environment (-24℃-4℃), the molecular chain movement ability of the rubber segment will weaken as the temperature decreases. As a result, when the temperature drops, the SEBS material can maintain a certain degree of flexibility, but its low temperature resistance is relatively limited. It can only meet the application scenarios with low requirements for low temperature performance (-18℃-4℃), but it cannot meet the application scenarios with resistance to lower temperatures (-60℃~-25℃). In addition, the SEBS material is prone to swelling when it comes into contact with oil substances, resulting in a decrease in its elasticity. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a door seal strip particle made of vinyl polyolefin elastomer, a preparation method, and a door seal strip, in order to at least partially solve the above technical problems. In this regard, the technical solution provided by the present invention is as follows.

[0005] As a first aspect of the present invention, a door seal strip particle made of vinyl polyolefin elastomer is provided. The door seal strip particle comprises, by weight: 20-50 parts of white mineral oil, 10-48 parts of polypropylene, 10-50 parts of vinyl polyolefin elastomer, 5-25 parts of calcium carbonate, 0-0.1 parts of antioxidant, and 0-0.1 parts of lubricant; wherein the degree of branching of the vinyl polyolefin elastomer is 70-130 branches / 1000 carbons, the weight average molecular weight is 77,000-521,000, the molecular weight distribution index is 1.5-3.0, and the melt index is 1-10g / 10min.

[0006] As a second aspect of the present invention, a method for preparing door seal particles made of vinyl polyolefin elastomer material is provided, comprising: step (1) blending white mineral oil, polypropylene, vinyl polyolefin elastomer, calcium carbonate, an antioxidant, and a lubricant to obtain a mixture; and step (2) feeding the mixture into a twin-screw extruder for extrusion granulation to obtain door seal particles made of vinyl polyolefin elastomer material.

[0007] As a third aspect of the present invention, a door seal is provided. The door seal is prepared by using the door seal particles made of the vinyl polyolefin elastomer material.

[0008] In an embodiment of the present invention, vinyl polyolefin elastomer (EPOE) is mainly a polyolefin chain composed of carbon-carbon single bonds. The molecular chain is relatively flexible as a whole and has a lower glass transition temperature than SEBS. It can maintain good elasticity in a lower temperature (-60°C) environment when used as a raw material to prepare door seals. In addition, the molecular chain of EPOE is relatively regular, the molecular chains in the crystalline region are closely arranged, and the intermolecular forces are strong. This intermolecular force makes the door seals prepared using EPOE raw materials have certain physical strengths such as tensile strength and tear strength while being elastic. In addition, since EPOE does not contain unsaturated groups and has a stable molecular chain structure, the prepared door seal particles have good oil resistance and water vapor barrier weather resistance when facing water vapor, oil pollution, oxidation, light, etc. In addition, the method for preparing door seal particles made of vinyl polyolefin elastomer material of the present invention is relatively simple and low in cost. DETAILED DESCRIPTION

[0009] In the process of implementing the concept of the present invention, it is found that the existing formula for preparing door seal particles using TPE materials mainly includes: styrene-ethylene / butylene-styrene block copolymer (SEBS), white mineral oil, polypropylene (PP), polyethylene (PE), calcium carbonate and other additives. The ethylene / butylene rubber segment (EB) in the SEBS molecular structure provides elasticity. In a low temperature environment (-24℃-4℃), the molecular chain movement ability of the rubber segment will weaken as the temperature decreases. However, due to the presence of styrene blocks in the SEBS molecular chain segment, using it as a physical crosslinking point can limit the excessive convergence and hardening of the molecular chain to a certain extent, so that when the temperature drops, SEBS can still maintain a certain degree of flexibility, but its low temperature resistance is relatively limited. In the face of a lower temperature environment (such as -60℃), this rubber material often has problems such as poor sealing and buffer failure. In addition, when the SEBS material contacts oil substances, it is easy to swell, which easily leads to a decrease in its physical properties, such as changes in size and reduced elasticity. In addition, the preparation cost of the door seal particles of the TPE formula system is high and the processing fluidity is poor.

[0010] In view of the above problems, the present invention proposes to use EPOE as a raw material to prepare door seal particles, and utilizes the good elasticity and physical strength of EPOE and the lower glass transition temperature (T g -50℃~-70℃), so that the prepared EPOE door seal particles have the characteristics of resistance to lower temperatures (-60℃), and at the same time have good elasticity, physical strength and stability at lower temperatures (-60℃).

[0011] Specifically, as a first aspect of the present invention, a door seal particle made of vinyl polyolefin elastomer is provided. The door seal particle comprises, by weight: 20-50 parts of white mineral oil, 10-48 parts of polypropylene, 10-50 parts of vinyl polyolefin elastomer (EPOE), 5-25 parts of calcium carbonate, 0-0.1 parts of antioxidant, and 0-0.1 parts of lubricant; wherein the branching degree of EPOE is 70-130 branches / 1000 carbons, and the weight average molecular weight (M w ) is 77,000-521,000, molecular weight distribution index (PDI = M w / M n , M n The number average molecular weight is 1.5-3.0, and the melt index is 1-10g / 10min.

[0012] In an embodiment of the present invention, EPOE is mainly a polyolefin chain composed of carbon-carbon single bonds. The molecular chain is relatively flexible as a whole and has a lower glass transition temperature, so that this flexible molecular chain can maintain good elasticity even at lower temperatures, and the door seal prepared using EPOE also has better resistance to lower temperatures, and is not easy to deform or crack at lower temperatures. Furthermore, because the branching degree of EPOE is not less than 70 branches / 1000 carbons, the door seal particles prepared using EPOE are easier to post-process and modify, and are given more functions. The higher the branching degree and weight-average molecular weight of EPOE, the higher the grafting rate of the subsequent grafting reaction with the grafted material, so that the application effect and processing performance of the grafted product are better. The molecular weight distribution index (PDI=1.5-3.0) of EPOE is relatively narrow, indicating that the molecular weight and molecular chain of EPOE are close to the same, and the distribution is relatively uniform, which makes it have good tensile toughness and impact toughness, thereby ensuring that the door seal particles made of EPOE have better mechanical properties and processing properties, and are not prone to abnormal conditions such as excessive degradation or cross-linking. In addition, because the molecular chain size of EPOE is uniform and the winding of the molecular chain is relatively stable, the process of preparing door seal particles is more controllable and the quality of door seal particles is more stable. The melt index of EPOE is moderate. Too low or too high a melt index will affect the flow properties of the door seal particles, resulting in poor processing performance and more difficult molding.

[0013] In addition, because EPOE does not contain unsaturated groups (such as double bonds) that are easily oxidized and has a relatively stable molecular chain structure, the door seal particles prepared using EPOE have good acid and alkali corrosion resistance, oil resistance, weather resistance and good water vapor barrier properties.

[0014] According to an embodiment of the present invention, EPOE is selected from the one produced by Hefei Zhongke Kele New Materials Co., Ltd. The preparation of EPOE includes: catalyzing the polymerization reaction of ethylene monomer under the action of a late transition metal catalyst (i.e., the main catalyst) and a co-catalyst. Since only ethylene monomer is used as the raw material, the cost of synthesizing EPOE is significantly reduced, thereby reducing the cost of preparing door seal particles made of EPOE material. The late transition metal catalyst can be selected from an α-diimine nickel catalyst having a structure as shown in formula (1), or an α-diimine palladium catalyst in which nickel (Ni) is replaced by palladium (Pd); the co-catalyst is selected from at least one of alkyl aluminoxane and alkyl aluminum. Formula (1); where R 1 , R 8 are each independently selected from hydrogen, C 1 -C 6 Alkyl, halogen, halogen-substituted C 1 -C 6 Alkyl, nitro, C 1 -C 6Any of alkoxy and trifluoromethyl; R 2 , R 7 , R 9 , R 12 are each independently selected from hydrogen, C 1 -C 6 Alkyl, halogen, halogen-substituted C 1 -C 6 Alkyl; R 3 , R 6 , R 10 , R 11 are each independently selected from hydrogen, C 1 -C 6 Alkyl, halogen, halogen-substituted C 1 -C 6 Any of alkyl, phenyl, and diphenylmethyl, R 4 , R 5 are each independently selected from hydrogen, C 1 -C 6 Alkyl, C 1 -C 6 Halogenated alkyl, phenyl, C 6 -C 30 substituted phenyl, X is selected from halogen, C 1 -C 6 Alkanes, C 2 -C 6 The halogen is selected from Cl or Br.

[0015] According to an embodiment of the present invention, the door seal particles based on vinyl polyolefin elastomer material further include: 0.1-0.2 parts of initiator and 0.5-3 parts of grafted material, in parts by weight.

[0016] In the embodiment of the present invention, EPOE has a high branching degree (70-130 branches / 1000 carbons), which makes it easier to carry out grafting modification and can graft more grafts, so that the obtained door seal particles have better performance. Furthermore, according to different grafts, the door seal particles can be given different properties, such as antibacterial properties, wear resistance, hydrophobicity, etc.

[0017] According to an embodiment of the present invention, the degree of branching of EPOE is 70-130 branches / 1000 carbons, and the weight average molecular weight is 77,000-521,000; further, the degree of branching of EPOE is preferably 78-120 branches / 1000 carbons, the weight average molecular weight is 84,000-424,000, the molecular weight distribution index is 1.8-2.8, and the melt index is 2-6g / 10min; further, the degree of branching of EPOE is 80-110 branches / 1000 carbons, the weight average molecular weight is 162,000-384,000, the molecular weight distribution index is 2.0-2.6, and the melt index is 2.5-5g / 10min. The higher the degree of branching of EPOE, the easier it is for the door seal particles prepared by EPOE to be post-processed and modified, and to be endowed with richer functions. In addition, the high degree of branching of EPOE gives it good tolerance to a variety of chemicals, enabling it to maintain stable performance in harsher chemical environments, such as maintaining elasticity and physical strength in lower temperature environments (such as -60°C).

[0018] In the embodiments of the present invention, in terms of fluidity: the branched structure in EPOE will hinder the close stacking of molecular chains, so that the entanglement between molecular chains is relatively reduced, thereby increasing the fluidity of the polymer. When performing post-processing modification operations such as injection molding and extrusion, good fluidity facilitates the door seal particles to better fill the mold, pass through the die, etc., which is conducive to molding processing. In terms of reactive sites: a higher degree of branching means that there are more active sites at the ends of the branches on the molecular chain. When performing chemical modifications such as graft copolymerization and cross-linking reactions, more active sites can participate in the reaction, increase the probability and efficiency of the reaction, and can more conveniently introduce new functional groups or construct new structures to achieve a variety of modification purposes. In terms of flexibility and plasticity: a higher degree of branching makes the polymer molecular chain more stretched and loose, with better overall flexibility, and easier to change shape when subjected to external forces. Then, in post-processing processes such as blow molding and calendering, it can be more smoothly molded into the corresponding shape according to the process requirements, and has stronger plasticity.

[0019] According to an embodiment of the present invention, the white mineral oil can be selected from at least one of 3# white mineral oil, 5# white mineral oil, 7# white mineral oil, 10# white mineral oil, 15# white mineral oil, and 26# white mineral oil. The white mineral oil is mainly used for lubrication, waterproofing and moisture-proofing, adjusting the hardness of the door seal particles, improving the flexibility and elasticity of the door seal particles, and facilitating extrusion during the processing process.

[0020] According to an embodiment of the present invention, calcium carbonate is selected from at least one of light calcium carbonate, heavy calcium carbonate and nano calcium carbonate. Calcium carbonate is mainly used to enhance the physical properties (such as wear resistance, hardness and tear resistance) and stability of the door seal particles, improve processing performance and reduce costs.

[0021] According to an embodiment of the present invention, the polypropylene is selected from at least one of homopolymer polypropylene, block copolymer polypropylene, and random copolymer polypropylene. For example, the polypropylene can be selected from any one of K8003, K7227H, K9829H, Z30S, T30S, 500N, and F300M. These polypropylenes can be purchased commercially, and the parameters of the polypropylene can be queried.

[0022] According to an embodiment of the present invention, the antioxidant is selected from at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester (antioxidant 1010), β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl alcohol ester (antioxidant 1076), tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168), butylated hydroxytoluene, butylated hydroxyanisole, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 4,4'-thiobis(6-tert-butyl-m-cresol), dioctadecyl pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, dilauryl thiodipropionate, distearyl thiodipropionate, tris(nonylphenol)phosphite, and tris(nonylphenyl)phosphite. Antioxidants can effectively protect the door seal particles from being oxidized by air, thereby extending the service life of the door seal particles.

[0023] According to an embodiment of the present invention, the lubricant is selected from at least one of stearic acid, calcium stearate, zinc stearate, ethylene bis stearamide (EBS), paraffin, polyethylene wax (PE wax), oxidized polyethylene wax (OPE wax), fatty acid ester, pentaerythritol stearate (PETS), montan wax, silicone oil, magnesium stearate, barium stearate, N,N'-ethylene bisoleamide, stearic acid amide, erucic acid amide, liquid paraffin, and microcrystalline wax. Adding lubricants to the door seal particles can improve the fluidity and plasticity of the particles during the production process, reduce the friction resistance between the particles, and thus improve the preparation quality of the door seal particles; adding lubricants can also extend the service life of the door seal particles.

[0024] According to an embodiment of the present invention, the initiator is a peroxide. Further, the peroxide is selected from at least one of di-tert-butyl peroxide, dicumyl peroxide, tert-butyl cumyl peroxide, 1,1-di-tert-butyl peroxide-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-bis(tert-butyl peroxide) hexane, 2,5-dimethyl-2,5-di(tert-butyl peroxy)-3-hexyne, bis(tert-butyl peroxide isopropyl) benzene, 2,5-dimethyl-2,5-bis(benzoyl peroxy) hexane, tert-butyl peroxybenzoate, and tert-butyl peroxy 2-ethylhexyl carbonate. The initiator is mainly used to initiate the grafting reaction between EPOE and the grafted material, so that the door seal particles have richer properties, such as antibacterial properties, wear resistance, compatibility, etc., so as to have a wider range of application scenarios.

[0025] According to an embodiment of the present invention, the grafted material is selected from at least one of a compatible monomer, an antibacterial monomer, and a hydrophobic monomer. Further, the compatible monomer is selected from at least one of maleic anhydride, methacrylic acid, acrylic acid, itaconic acid, fumaric acid, isocyanate, glycidyl methacrylate, methyl methacrylate, dibutyl fumarate, β-hydroxyethyl methacrylate, dibutyl maleate, and diethyl maleate. Specifically, maleic anhydride: because maleic anhydride contains unsaturated double bonds and anhydride groups, EPOE can increase its reactivity after being grafted with maleic anhydride, and can react with other substances containing active groups, thereby improving its compatibility and adhesion with other materials. Methacrylic acid: because it contains carboxyl groups, it can provide an acidic environment, react with alkaline substances, and can also improve the adsorption performance of EPOE and its compatibility with other materials containing functional groups. Acrylic acid, itaconic acid and fumaric acid: contain carboxyl groups, which can enhance the acidity of EPOE, making it more compatible with some alkaline additives and used to adjust the pH. Isocyanate: After grafting, it can react with compounds containing active hydrogen (such as hydroxyl, amino group), and increase the cross-linking density by forming urea bonds or urethane bonds, thereby improving the strength and wear resistance of the door seal particles. Glycidyl methacrylate: After grafting, its epoxy group can react with substances containing active hydrogen (such as hydroxyl, amino group, etc.), and the double bonds it contains can participate in the polymerization reaction, so that reactive groups can be introduced to prepare materials with special functions, such as improving the adhesion and chemical stability of door seal particles. Methyl methacrylate: After grafting, it can increase the hardness and transparency of door seal particles. Dibutyl fumarate: The ester group it contains can reduce the glass transition temperature after grafting, and it can still maintain a certain flexibility at low temperatures (such as -60°C), and can improve the processing performance of door seal particles. β-Hydroxyethyl methacrylate: It contains hydroxyl groups to provide reactivity and can react with other materials containing functional groups, such as isocyanate, and is used to prepare door seal particles with good flexibility and adhesion. Dibutyl maleate: The ester group it contains reduces the rigidity of the material, making it easier to process and shape. After grafting, it can reduce the rigidity of the door seal particles, making it easier to process and shape. Diethyl maleate: After grafting, the ester group reduces the hardness of EPOE and improves its flexibility. In addition, because it contains double bonds, it can change the molecular structure of EPOE during the polymerization reaction and increase the compatibility of EPOE with other organic components.

[0026] According to an embodiment of the present invention, the sulfide may be selected from sulfur dioxide or sulfenyl chloride. After the sulfur compound is grafted, the oxidation resistance and stability of the door seal particles may be improved, thereby extending the service life of the door seal particles.

[0027] According to an embodiment of the present invention, the antibacterial monomer is selected from quaternary ammonium salts or phenols, wherein the quaternary ammonium salt group or the phenolic hydroxyl group can play an antibacterial role, inhibit the growth and reproduction of bacteria, thereby achieving the purpose of antibacterial. Therefore, by adding the antibacterial monomer, the obtained door seal particles have antibacterial properties. Further, the quaternary ammonium salt is selected from at least one of methacryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride, dimethyl diallyl ammonium chloride, methacryloyloxyethyl benzyl dimethyl ammonium chloride, and methacryloyloxyethyl-m-chlorobenzyl-dimethyl ammonium chloride. Phenols are selected from at least one of p-vinylphenol, p-hydroxyphenyl methacrylate, o-cresol, m-cresol, p-cresol, and bisphenol A.

[0028] According to an embodiment of the present invention, the hydrophobic monomer is selected from at least one of polydimethylsiloxane alcohol, lactic acid-modified siloxane, amino acid-modified siloxane, starch-modified siloxane, cellulose-modified siloxane, chitosan-modified siloxane, fatty acid-modified siloxane, terpene-modified siloxane, lignin-modified siloxane, protein-modified siloxane, polydimethylsiloxane, cyclic polydimethylsiloxane, phenyl polytrimethylsiloxane, methyl-vinyl siloxane, diphenyl siloxane, methyloctyl siloxane, hydroxy-terminated ethoxypropoxylated-dimethylsiloxane, octa(trimethylsiloxane)silsesquioxane, and γ-glycidyloxypropyl trimethoxysiloxane.

[0029] As a second aspect of the present invention, a method for preparing door seal particles made of vinyl polyolefin elastomer material in the above-mentioned embodiment is provided, comprising: step (1) blending white mineral oil, polypropylene, EPOE, calcium carbonate, an antioxidant, and a lubricant to obtain a mixture; and step (2) feeding the mixture into a twin-screw extruder for extrusion granulation to obtain door seal particles made of vinyl polyolefin elastomer material.

[0030] In an embodiment of the present invention, white mineral oil, polypropylene, EPOE, calcium carbonate, antioxidant, and lubricant are weighed in proportion, mixed evenly, and then extruded and granulated to prepare door seal particles. The preparation method is relatively simple, has high fluidity, and low cost.

[0031] For example: by weight, 25 parts of white mineral oil, 30 parts of polypropylene, 20 parts of EPOE, 25 parts of calcium carbonate, 0.1 parts of antioxidant, and 0.1 parts of lubricant are blended in a three-dimensional blender for 2-4 hours to obtain a mixture. After the white mineral oil is fully absorbed, the mixture is put into a twin-screw extruder for extrusion granulation to obtain EPOE door seal particles. Among them, the aspect ratio of the twin-screw extruder is greater than or equal to 45, the temperature of each zone of the twin-screw extruder is preferably 150℃-220℃, the feeding speed of the twin-screw extruder is greater than or equal to 20Hz, and the main engine speed of the twin-screw extruder is greater than or equal to 400r / min.

[0032] According to an embodiment of the present invention, step (1) also includes: adding an initiator and a grafted material, so as to initiate a grafting reaction between EPOE and the grafted material through the initiator, so that EPOE has richer properties. Specifically, in another embodiment, a method for preparing door seal particles made of vinyl polyolefin elastomer material includes: in the presence of an initiator, the grafted material and EPOE are subjected to a grafting reaction to form a vinyl polyolefin elastomer-grafted material, and then blended with white mineral oil, polypropylene, calcium carbonate, antioxidant, and lubricant to obtain a mixed material. Subsequently, the mixed material is put into a twin-screw extruder for extrusion granulation to obtain door seal particles made of vinyl polyolefin elastomer material containing the grafted material. It should be noted that the amounts of EPOE, white mineral oil, polypropylene, calcium carbonate, antioxidant, lubricant, etc. involved in the method for preparing door seal particles made of vinyl polyolefin elastomer material in this embodiment are as described in the above embodiment, and will not be described in detail here.

[0033] For example, 100 parts of EPOE, 0.1 parts of initiator and 0.5 parts of grafted material are weighed by weight for grafting reaction to obtain vinyl polyolefin elastomer-grafted material. Subsequently, 25 parts of white mineral oil, 30 parts of polypropylene, 20 parts of vinyl polyolefin elastomer-grafted material, 25 parts of calcium carbonate, 0.1 parts of antioxidant and 0.1 parts of lubricant are weighed and blended in a three-dimensional blender for 2-4 hours to obtain a mixed material. The mixed material is put into a twin-screw extruder for extrusion granulation to obtain vinyl polyolefin elastomer door seal particles containing grafted material.

[0034] As a third aspect of the present invention, a door seal is provided, which is prepared using the door seal particles made of vinyl polyolefin elastomer material in the above embodiment.

[0035] In an embodiment of the present invention, a door seal prepared using the door seal particles provided by the present invention can withstand lower temperatures (-60°C) and maintain good elasticity and physical strength; the door seal is relatively stable when facing water vapor, oil stains, oxidation, light, etc.

[0036] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0037] Experimental test methods

[0038] Melt flow rate (i.e. melt index, in g / 10min), is the number of grams of molten material (such as door seal particles or vinyl polyolefin elastomer) that flows out through a standard capillary within 10min under the test conditions of 190℃ and 5kg. For specific testing standards, please refer to Table 3.

[0039] Antibacterial rate test: The film contact antibacterial test method is adopted, that is, a film containing bacteria is pasted on the sample to be tested (such as door seals), and the growth of bacteria is observed after a period of incubation. The antibacterial rate is calculated by comparing the bacterial growth of the control group and the test group. For specific detection standards, please refer to Table 3.

[0040] Water vapor barrier performance test: It is an electrolytic sensor method, that is, by measuring the current change caused by the difference in water vapor concentration on both sides of the material (such as door seal), the water vapor transmission rate is calculated to evaluate the water vapor barrier performance of the material. For specific testing standards, please refer to Table 3.

[0041] Oil stain resistance test: The door seal particles are made into dumbbell-shaped specimens with a middle parallel part (narrow part) of 115 mm in length, 6 mm in width and 0.5 mm in thickness. After being fully immersed in edible blended oil for 24 hours, the changes in mechanical properties before and after immersion are tested. For specific testing standards, refer to Table 3.

[0042] Example 1

[0043] The door seal particles made of vinyl polyolefin elastomer (EPOE) include, by weight: 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of EPOE, 0.05 parts of antioxidant 1010 (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester), 0.05 parts of antioxidant 168 (tris[2,4-di-tert-butylphenyl] phosphite), and 0.1 parts of lubricant ethylene bisstearamide (EBS). Among them, the branching degree of EPOE is around 95 branches / 1000 carbons, the weight average molecular weight is around 300,000, the molecular weight distribution index PDI is around 2.6, and the melt index is around 5g / 10min (190℃, 2.16kg).

[0044] The method for preparing door seal particles made of vinyl polyolefin elastomer (EPOE) includes: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of EPOE, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant EBS in a three-dimensional blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain EPOE door seal particles. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0045] Furthermore, the door seal particles obtained in Example 1 were prepared into door seals and their performance was tested. The specific test results are shown in Table 1, wherein Table 3 shows the standards for various technical indicators of the door seal, including hardness, melt flow rate, tensile strength, elongation at break and density, as well as reference testing standards.

[0046] Example 2

[0047] The antibacterial vinyl polyolefin elastomer (EPOE-1) includes, by weight, 100 parts of EPOE, 0.15 parts of di-tert-butyl peroxide (initiator), and 1.5 parts of methacryloyloxyethyl trimethyl ammonium chloride (antibacterial monomer). The branching degree of EPOE is around 95 branches / 1000 carbons, the weight average molecular weight is around 300,000, the molecular weight distribution index PDI is around 2.6, and the melt index is around 5g / 10min (190°C, 2.16kg).

[0048] The method for preparing an antibacterial vinyl polyolefin elastomer (EPOE-1) comprises: weighing 100 parts of EPOE, 0.15 parts of di-tert-butyl peroxide, and 1.5 parts of methacryloyloxyethyl trimethyl ammonium chloride (antibacterial monomer) in a three-dimensional mixer and mixing them thoroughly for 30 minutes, then taking out the obtained mixture and putting it into a twin-screw extruder that has been heated in advance for melt extrusion granulation to obtain an antibacterial vinyl polyolefin elastomer, named EPOE-1. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0049] The method for preparing door seal particles of vinyl polyolefin elastomer (EPOE-1) material with antibacterial properties comprises: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of EPOE-1, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant EBS in a three-dimensional blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain door seal particles of EPOE-1 material. The aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150°C-220°C, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0050] Furthermore, the door seal particles obtained in Example 2 were prepared into door seals and their performance was tested. The specific test results are shown in Table 1.

[0051] Example 3

[0052] The difference between Example 3 and Example 2 is that the door seal particles are made of vinyl polyolefin elastomer (EPOE-2) with oil resistance and water vapor barrier properties, and the specific preparation process is as follows.

[0053] The vinyl polyolefin elastomer (EPOE-2) with oil resistance and water vapor barrier includes, by weight, 100 parts of EPOE, 0.15 parts of di-tert-butyl peroxide (initiator), and 1.5 parts of polydimethylsiloxane (hydrophobic monomer). Among them, the branching degree of EPOE is around 95 branches / 1000 carbons, the weight average molecular weight is around 300,000, the molecular weight distribution index PDI is around 2.6, and the melt index is around 5g / 10min (190℃, 2.16kg).

[0054] The method for preparing a vinyl polyolefin elastomer (EPOE-2) with oil resistance and water vapor barrier includes: weighing 100 parts of EPOE, 0.15 parts of di-tert-butyl peroxide, and 1.5 parts of polydimethylsiloxane in a three-dimensional mixer and mixing them thoroughly for 30 minutes, taking out the obtained mixture and putting it into a twin-screw extruder that has been heated in advance for melt extrusion granulation to obtain a vinyl polyolefin elastomer with oil resistance and water vapor barrier, named EPOE-2. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0055] The method for preparing door seal particles of vinyl polyolefin elastomer (EPOE-2) material with oil resistance and water vapor barrier includes: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of EPOE-2, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant EBS in a three-dimensional integrated blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain EPOE-2 door seal particles. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0056] Furthermore, the door seal particles obtained in Example 3 were prepared into door seals and their performance was tested. The specific test results are shown in Table 1.

[0057] Comparative Example 1

[0058] The door seal particles made of SEBS thermoplastic elastomer include, by weight: 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 15 parts of SEBS, 5 parts of EVA, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant ethylene bis stearamide (EBS). Among them, SEBS thermoplastic elastomer uses 250N from Celanese Corporation of the United States.

[0059] The method for preparing door seal particles made of SEBS thermoplastic elastomer material includes: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 15 parts of SEBS, 5 parts of EVA, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant EBS in a three-dimensional integrated blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain door seal particles made of SEBS thermoplastic elastomer material. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0060] Furthermore, the door seal particles obtained in Comparative Example 1 were prepared into door seals and their performance was tested. The specific test results are shown in Table 1.

[0061] Comparative Example 2

[0062] The door seal particles made of polyolefin elastomer (POE) include, by weight: 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of POE, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant ethylene bis stearamide (EBS). Among them, the polyolefin elastomer (POE) uses POE-8200 from Dow Chemical Company of the United States.

[0063] The method for preparing door seal particles made of polyolefin elastomer (POE) includes: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of POE, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant ethylene bis stearamide (EBS) in a three-dimensional integrated blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain POE door seal particles. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0064] Furthermore, the door seal particles obtained in Comparative Example 2 were prepared into door seals and their performance was tested. The specific test results are shown in Table 1.

[0065] Comparative Example 3

[0066] The antibacterial SEBS thermoplastic elastomer (SEBS-1) comprises, by weight: 100 parts of SEBS thermoplastic elastomer, 0.15 parts of di-tert-butyl peroxide (initiator), and 1.5 parts of methacryloyloxyethyl trimethylammonium chloride, wherein the SEBS thermoplastic elastomer is selected from 250N of Celanese Corporation of the United States.

[0067] The method for preparing an antibacterial SEBS polyolefin elastomer (SEBS-1) comprises: weighing 100 parts of SEBS thermoplastic elastomer, 0.15 parts of di-tert-butyl peroxide, and 1.5 parts of methacryloyloxyethyl trimethyl ammonium chloride in a three-dimensional mixer and mixing them thoroughly for 30 minutes, taking out the obtained mixture and putting it into a twin-screw extruder that has been heated in advance for melt extrusion granulation to obtain an antibacterial SEBS thermoplastic elastomer, named SEBS-1. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0068] The method for preparing door seal particles of SEBS thermoplastic elastomer (SEBS-1) material with antibacterial properties comprises: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of SEBS-1, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant EBS in a three-dimensional blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain door seal particles of SEBS-1 thermoplastic elastomer material. The aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150°C-220°C, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0069] Furthermore, the door seal particles obtained in Comparative Example 3 were prepared into door seals and their performance was tested. The specific test results are shown in Table 2.

[0070] Comparative Example 4

[0071] The difference between Comparative Example 4 and Comparative Example 3 is that the door seal particles are made of SEBS thermoplastic elastomer (SEBS-2) with oil resistance and water vapor barrier, and the specific preparation process is as follows.

[0072] The oil-resistant and water vapor barrier SEBS thermoplastic elastomer (SEBS-2) comprises, by weight: 100 parts of SEBS thermoplastic elastomer, 0.15 parts of di-tert-butyl peroxide (initiator), and 1.5 parts of polydimethylsiloxane, wherein the SEBS thermoplastic elastomer is selected from 250N produced by Celanese Corporation of the United States.

[0073] The method for preparing a SEBS thermoplastic elastomer (SEBS-2) with oil resistance and water vapor barrier includes: weighing 100 parts of SEBS thermoplastic elastomer, 0.15 parts of di-tert-butyl peroxide, and 1.5 parts of polydimethylsiloxane in a three-dimensional mixer and mixing them thoroughly for 30 minutes, taking out the obtained mixture and putting it into a twin-screw extruder that has been heated in advance for melt extrusion granulation to obtain a SEBS thermoplastic elastomer with oil resistance and water vapor barrier, named SEBS-2. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0074] The method for preparing door seal particles made of SEBS thermoplastic elastomer (SEBS-2) material with oil resistance and water vapor barrier includes: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of SEBS-2, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant ethylene bis stearamide (EBS) in a three-dimensional integrated blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain door seal particles made of SEBS-2 thermoplastic elastomer. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0075] Furthermore, the door seal particles obtained in Comparative Example 4 were prepared into door seals and their performance was tested. The specific test results are shown in Table 2.

[0076] Comparative Example 5

[0077] The antibacterial POE polyolefin elastomer (POE-1) includes, by weight: 100 parts of POE polyolefin elastomer, 0.15 parts of di-tert-butyl peroxide (initiator), and 1.5 parts of methacryloyloxyethyl trimethyl ammonium chloride. Among them, the POE polyolefin elastomer uses POE-8200 produced by Dow Chemical Company of the United States, with a molecular weight distribution PDI of about 2.6 and a melt index of about 5g / 10min (190°C, 2.16kg).

[0078] The method for preparing an antibacterial POE polyolefin elastomer (POE-1) comprises: weighing 100 parts of POE polyolefin elastomer, 0.15 parts of di-tert-butyl peroxide, and 1.5 parts of methacryloyloxyethyl trimethyl ammonium chloride in a three-dimensional mixer and mixing them thoroughly for 30 minutes, taking out the obtained mixture and putting it into a twin-screw extruder that has been heated in advance for melt extrusion granulation to obtain an antibacterial POE polyolefin elastomer, named POE-1. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0079] The method for preparing door seal particles of POE polyolefin elastomer (POE-1) material with antibacterial properties comprises: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of POE-1, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant EBS in a three-dimensional blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain door seal particles of POE-1 material. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0080] Furthermore, the door seal particles obtained in Comparative Example 5 were prepared into door seals and their performance was tested. The specific test results are shown in Table 2.

[0081] Comparative Example 6

[0082] The difference between Comparative Example 6 and Comparative Example 5 is that the door seal particles are made of POE polyolefin elastomer (POE-2) material that is resistant to oil stains and has a water vapor barrier property, and the specific preparation process is as follows.

[0083] The POE polyolefin elastomer (POE-2) with oil resistance and water vapor barrier comprises, by weight: 100 parts of POE, 0.15 parts of di-tert-butyl peroxide (initiator), and 1.5 parts of polydimethylsiloxane, wherein the POE polyolefin elastomer is selected from POE-8200 produced by Dow Chemical Company of the United States.

[0084] The method for preparing a POE polyolefin elastomer (POE-2) with oil resistance and water vapor barrier includes: weighing 100 parts of POE polyolefin elastomer, 0.15 parts of di-tert-butyl peroxide, and 1.5 parts of polydimethylsiloxane in a three-dimensional mixer and mixing them thoroughly for 30 minutes, taking out the obtained mixture and putting it into a twin-screw extruder that has been heated in advance for melt extrusion granulation to obtain a POE polyolefin elastomer with oil resistance and water vapor barrier, named POE-2. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0085] The method for preparing door seal particles of POE polyolefin elastomer (POE-2) material with oil resistance and water vapor barrier includes: weighing 25 parts of 10# white mineral oil, 30 parts of polypropylene K7227H, 25 parts of heavy calcium carbonate, 20 parts of POE-2, 0.05 parts of antioxidant 1010, 0.05 parts of antioxidant 168, and 0.1 parts of lubricant EBS in a three-dimensional integrated blender, and blending for 4 hours. After the 10# white mineral oil is fully absorbed, the obtained mixture is put into a twin-screw extruder for melt extrusion granulation to obtain door seal particles of POE-2 material. Among them, the aspect ratio of the twin-screw extruder is 45, the temperature of each zone of the twin-screw extruder is 150℃-220℃, the feeding speed of the twin-screw extruder is 20Hz, and the main engine speed of the twin-screw extruder is 400r / min.

[0086] Furthermore, the door seal particles obtained in Comparative Example 6 were prepared into door seals and their performance was tested. The specific test results are shown in Table 2.

[0087] Table 1

[0088]

[0089] Table 2

[0090]

[0091] Table 3

[0092]

[0093] From the comparison of Tables 1 to 3, it can be seen that the product performance indicators such as density, melt flow rate, hardness, tensile strength and elongation at break of the door seals prepared by Examples 1-3 and Comparative Examples 1-6 of the present invention all meet the standards of various indicators, which shows that the door seals prepared by Examples 1-3 of the present invention have excellent performance and can be used in practice. Further, after comparing the data in Example 1 and Comparative Example 1, it can be found that after all SEBS is replaced by EPOE, the various indicators of the prepared door seal particles are on an upward trend, indicating that the strategy of using EPOE to replace SEBS to prepare door seals is feasible. Further, by comparing Example 1 with Comparative Example 2, it can be seen that the various properties of the door seals prepared by EPOE are comparable to those of the door seals prepared by POE. However, POE is a copolymer of ethylene and α-olefins (such as 1-octene), while EPOE in the present invention is an ethylene polymer, which is lower in cost than POE and is expected to replace POE materials to prepare door seals. Furthermore, compared with POE, EPOE has a higher degree of branching and is easier to be grafted and modified. Depending on the grafted material, different properties can be given to the door seal particles, such as antibacterial properties, oil resistance, high water vapor barrier and other unique properties. For example, the door seal particles prepared by grafting antibacterial agents in EPOE have significantly improved antibacterial properties (such as Examples 1-2 and Comparative Examples 3 and Comparative Example 5); the door seal particles prepared by grafting polydimethylsiloxane in EPOE have significantly improved water vapor barrier properties and reduced performance loss before and after oil immersion (such as Examples 1 and 3 and Comparative Examples 4 and Comparative Example 6), which further indicates that compounds grafted with different groups of EPOE can give door seals unique properties. Furthermore, since EPOE has no unsaturated bonds, compared with SEBS, it can improve the weather resistance and aging resistance of door seal materials and extend their service life.

[0094] Furthermore, the hardness change rate of each embodiment and comparative example was measured and compared. Before the test, the hardness of the door seal before being placed in the refrigerator was measured first, and then the hardness of the door seal after being placed in a refrigerator at -25°C, -30°C, -40°C, and -60°C for 6 hours was measured in turn, and the change rate of the door seal hardness was calculated. The specific test results are shown in Table 4.

[0095] Table 4

[0096]

[0097] It can be seen from Table 4 that the door seal made of vinyl polyolefin elastomer provided by the present invention has low temperature resistance (-25°C~-60°C).

[0098] In summary, the present invention uses EPOE (vinyl polyolefin elastomer) as a raw material to prepare door seal particles, which has the following effects on the components.

[0099] (1) Improved flexibility: EPOE can make products made of door seal strip particles more elastic and flexible, which helps the door seal strip to better fit and seal and adapt to different usage conditions.

[0100] (2) Enhanced impact resistance: EPOE helps to improve the overall impact resistance of the door seal, making it less likely to break when subjected to external force such as during daily door opening and closing.

[0101] (3) Optimizing compatibility: EPOE can improve the compatibility between different components through grafting reactions, making the entire door seal particle system more evenly and stably mixed, thereby ensuring the performance stability and quality consistency of the door seal. Specifically, through grafting reactions, EPOE is grafted with functional groups that can react chemically with other components, such as grafted maleic anhydride. When blended with polymers containing reactive groups, chemical bonds can be formed at the interface, strengthening the connection between the two and improving compatibility. The grafted EPOE also changes its original surface properties, reducing the interfacial tension between it and other blended components, allowing different phases to be better dispersed and fused, preventing phase separation, and improving compatibility. The grafted chain can interact with the molecules of other components through intermolecular forces such as van der Waals forces and hydrogen bonds, making the molecules of different components more tightly bound, which is conducive to uniform dispersion in the system, and thus can also improve compatibility.

[0102] (4) Adjusting hardness: EPOE can properly adjust the hardness of the door seal particles to achieve an appropriate hardness range to meet the requirements for touch and sealing effect in actual use.

[0103] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A door seal particle made of vinyl polyolefin elastomer, characterized in that: In parts by weight, the door seal particles include: 20-50 parts of white mineral oil, 10-48 parts of polypropylene, 10-50 parts of vinyl polyolefin elastomer, 5-25 parts of calcium carbonate, 0-0.1 parts of antioxidant, 0-0.1 parts of lubricant; The vinyl polyolefin elastomer has a branching degree of 70-130 branches / 1000 carbons, a weight average molecular weight of 77,000-521,000, a molecular weight distribution index of 1.5-3.0, and a melt index of 1-10 g / 10 min.

2. The door seal strip particles according to claim 1, characterized in that: In parts by weight, the door seal particles also include: 0.1-0.2 parts of initiator and 0.5-3 parts of grafted material.

3. The door seal strip particles according to claim 1, characterized in that: The vinyl polyolefin elastomer has a branching degree of 78-120 branches / 1000 carbons, a weight average molecular weight of 84,000-424,000, a molecular weight distribution index of 1.8-2.8, and a melt index of 2-6 g / 10 min.

4. The door seal strip particles according to claim 1, characterized in that: The vinyl polyolefin elastomer has a branching degree of 80-110 branches / 1000 carbons, a weight average molecular weight of 162,000-384,000, a molecular weight distribution index of 2.0-2.6, and a melt index of 2.5-5 g / 10 min.

5. The door seal strip particles according to claim 1 or 2, characterized in that: The calcium carbonate is selected from at least one of light calcium carbonate, heavy calcium carbonate and nano calcium carbonate; The polypropylene is selected from at least one of homopolymer polypropylene, block copolymer polypropylene and random copolymer polypropylene; The antioxidant is selected from at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate octadecyl, tris[2,4-di-tert-butylphenyl]phosphite, dibutylhydroxytoluene, butylated hydroxyanisole, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 4,4'-thiobis(6-tert-butyl-m-cresol), dioctadecyl pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, dilauryl thiodipropionate, distearyl thiodipropionate, tris(nonylphenol)phosphite, and tris(nonylphenyl)phosphite; The lubricant is selected from at least one of stearic acid, calcium stearate, zinc stearate, ethylene bisstearamide, paraffin, polyethylene wax, oxidized polyethylene wax, fatty acid ester, pentaerythritol stearate, montan wax, silicone oil, magnesium stearate, barium stearate, N,N'-ethylene bisoleamide, stearic acid amide, erucic acid amide, liquid paraffin, and microcrystalline paraffin.

6. The door seal strip particles according to claim 2, characterized in that: The initiator is a peroxide, and the peroxide is selected from at least one of di-tert-butyl peroxide, dicumyl peroxide, tert-butyl cumyl peroxide, 1,1-di-tert-butyl peroxy-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane, 2,5-dimethyl-2,5-di(tert-butyl peroxy)-3-hexyne, bis(tert-butyl peroxyisopropyl)benzene, 2,5-dimethyl-2,5-bis(benzoyl peroxy)hexane, tert-butyl peroxybenzoate, and tert-butyl peroxy 2-ethylhexyl carbonate; The grafted substance is selected from at least one of a compatible monomer, an antibacterial monomer, a hydrophobic monomer and a sulfide.

7. The door seal strip particles according to claim 6, characterized in that: The compatible monomer is selected from at least one of maleic anhydride, methacrylic acid, acrylic acid, itaconic acid, fumaric acid, isocyanate, glycidyl methacrylate, methyl methacrylate, dibutyl fumarate, β-hydroxyethyl methacrylate, dibutyl maleate and diethyl maleate; The antibacterial monomer is selected from quaternary ammonium salts or phenols, wherein the quaternary ammonium salt is selected from at least one of methacryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride, dimethyl diallyl ammonium chloride, methacryloyloxyethyl benzyl dimethyl ammonium chloride, and methacryloyloxyethyl-m-chlorobenzyl-dimethyl ammonium chloride; the phenol is selected from at least one of p-vinylphenol, p-hydroxyphenyl methacrylate, o-cresol, m-cresol, p-cresol, and bisphenol A; The hydrophobic monomer is selected from at least one of polydimethylsiloxane alcohol, lactic acid modified siloxane, amino acid modified siloxane, starch modified siloxane, cellulose modified siloxane, chitosan modified siloxane, fatty acid modified siloxane, terpene modified siloxane, lignin modified siloxane, protein modified siloxane, polydimethylsiloxane, cyclic polydimethylsiloxane, phenyl polytrimethylsiloxane, methyl-vinyl siloxane, diphenyl siloxane, methyloctyl siloxane, hydroxyl-terminated ethoxypropoxylated-dimethylsiloxane, octa(trimethylsiloxane)silsesquioxane, and γ-glycidyloxypropyl trimethoxysiloxane.

8. A method for preparing the door seal particles made of vinyl polyolefin elastomer according to any one of claims 1 to 7, characterized in that: The preparation method comprises: Step (1) blending white mineral oil, polypropylene, vinyl polyolefin elastomer, calcium carbonate, antioxidant and lubricant to obtain a mixed material; Step (2) feeding the mixed material into a twin-screw extruder for extrusion granulation to obtain vinyl polyolefin elastomer door seal particles.

9. The preparation method according to claim 8, characterized in that: The step (1) further comprises: adding an initiator and a grafted substance; Wherein, in the presence of the initiator, the grafted product and the vinyl polyolefin elastomer undergo a grafting reaction to form a vinyl polyolefin elastomer-grafted product, which is then blended with the white mineral oil, polypropylene, calcium carbonate, antioxidant and lubricant to obtain a mixed material.

10. A door seal, characterized in that: The door seal strip particles are prepared using the vinyl polyolefin elastomer material described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Environmental protection type SEBS thermoplastic elastic body sealing strip material and preparation method thereof

    CN101100593A

  • Thermoplastic polyurethane elastomer (TPE) door seal for refrigerator and freezer and preparation method thereof

    CN102532778A

  • Cross-linked olefin thermal shrinkage film with antibacterial function and preparation method thereof

    CN111635570A

  • Polypropylene material and preparation method thereof

    CN116478473A

  • Application of vinyl polyolefin elastomer in toughening polypropylene

    CN117247481A

Cited By

  • Preparation method of anti-aging high-density polyethylene composite material for pipelines

    CN120518940A

  • Dynamic vulcanized rubber as well as preparation method and application thereof

    CN121226946A